Using Traditional Knowledge to Adapt to Ecological Change: Denésoliné Monitoring of Caribou Movements - Parlee, Brenda; Manseau, Micheline; Dene First Nation, Lutsël K'é (ARCTIC, 2010)
The Chipewyan Dene or Denésoliné have long been dealing with variability in the movements of barren-ground caribou (Rangifer tarandus). Many generations ago, Denésoliné hunters learned that by observing caribou at key water crossings during the fall migration, they could obtain critical information about caribou health, population, and movement patterns. Systematic observation of these indicators by hunters strategically organized along the tree line enabled the Denésoliné to adapt their harvesting practices, including the location of family camps, to maximize harvest success. While this system of observation was developed for traditional subsistence harvesting, its techniques could be usefully applied today to other natural resource management contexts. In particular, such monitoring might help us understand how new bifurcation points created by mineral resource development may be affecting the Bathurst caribou herd. As governments, communities, and academics search for ways to include traditional knowledge in decision making for resource management, this paper recognizes that the Denésoliné and other indigenous peoples have their own systems of watching, listening, learning, understanding, and adapting to ecological change. Les Dénés Chipewyans ou Denésoliné ont eu depuis longtemps à faire face à la variabilité dans les déplacements du caribou de la toundra (Rangifer tarandus). Il y a de cela des générations, les chasseurs Denésoliné ont appris qu’en observant le caribou aux traversées majeures de cours d’eau durant la migration automnale, ils obtenaient de l’information critique sur la santé et la population de caribou, ainsi que sur ses habitudes migratoires. L’observation systématique de ces indicateurs par des chasseurs placés de façon stratégique le long de la ligne des arbres permettait aux Denésoliné d’adapter leurs pratiques de prélèvement, y compris l’emplacement des camps pour leur famille, afin d’optimiser le succès de la récolte. Si ce système d’observation a été mis au point pour la récolte de ...